Intestinal expression of pro-inflammatory cytokines induced by oral intake of lipopolysaccharide (LPS) from E. coli in weaned pigs (2012)
ABSTRACT: treatments with lipopolysaccharide (LPS) from E. coli are an accepted way of inducing inflammation in immunological studies since they have the ability to activate a coordinate series of signs through the synthesis of pro-inflammatory cytokines such as interleukin 8 (IL-8), IL-18 and tumor necrosis factor alpha (TNF-α), which can cause significant changes in intestinal structure and functionality. Objective: the aim of this study was to evaluate the effect of adding LPS of E. coli on pro-inflammatory cytokine gene expression IL-8, IL-18 and TNF-α in early-weaned pigs. Methods: fieldwork was conducted at Centro San Pablo, belonging to the Universidad Nacional de Colombia with 32 pigs at 21 days of age, with 6.5 ± 0.5 kg of weight. Animals were fed with a basal diet supplemented with two levels of inclusion of LPS of E. coli serotype 0111:B4 (0 to 0.3 μg/mg of food). Pigs were slaughtered in stages on days 1, 5, 7 and 10 postweaning and complete extraction of small intestine was made. Gene expression was evaluated by qPCR. Blocks at random in a factorial arrangement 2 x 4 were used as statistical design. Results: the basal diet (without addition of LPS) presented increase in mRNA expression (p<0.01) of all the cytokines in jejunum for each post-weaning day, which suggests an inflammatory response and extensive tissue damage in pigs after early weaning. In diet 1 (with consumption of 0.3 μg LPS / mg diet) cytokines TNF-α, IL-8 and IL- 18 showed a significant increase in their levels of expression (p<0.01). All cytokines presented significant increase (p<0.01) in jejunum for each post-weaning day. Conclusion: The increase observed in the expression of TNF-α can be involved in the development of post-weaning diarrhea.